Orotraqueal intubation training in the coronavirus pandemic: application of the rapid cycle deliberate practice - André,Rodrigo Pereira Diaz (2021)
Abstract: Introduction: the coronavirus pandemic disclosed the need for safe orotracheal intubation not only for the patient, but also for the professionals involved in the procedure. Therefore, training and technique reviews became necessary. Objective: this article aims to propose the application of the Rapid Cycle Deliberate Practice (RCDP) strategy for the training of anesthesiologists in orotracheal intubation in people with confirmed or suspected COVID-19 and to present a guide for the application of this strategy in this situation. Method: This is a methodological study presenting the theoretical and operational aspects for the Rapid Cycle Deliberate Practice application and a guide constructed from the search for evidence published in journals and official recommendations published by the institutions linked to the Brazilian and international health area. Results: the main theoretical aspects reported are related to the three principles on which Rapid Cycle Deliberate Practice is based: maximizing time in deliberate practice, targeted feedback, and explicit psychological security. As for the operational aspects, it is highlighted that the training must be carried out with a maximum of six people. An error must be interrupted, prescriptive feedback must be given, and the task must be performed again until the participant reaches mastery. As for the procedure technical specificity, a guide to the application of the rapid cycle deliberate practice is presented with the sequence for the adequate airway management of hypoxemic patients with suspected or confirmed COVID-19 infection. Conclusion: it is concluded that the assessed instructional strategy showed to be promising for the training with mastery learning in all professionals who will perform the procedure of orotracheal intubation while facing the severe forms of COVID-19, minimizing the risk of contamination.